EFEKTIVITAS PEMBERIAN PISANG AMBON (MUSA PARADISIACAL) DENGAN VITAMIN B6 DALAM MENURUNKAN INTENSITAS MUAL MUNTAH PADA IBU HAMIL TM 1 DI KLINIK LINA HINAI KIRI KEC.SECANGGANG - Khairani; Maidina Putri (Jurnal Ilmiah Kebidanan Imelda, 2022)
Nausea (nausea) and vomiting (emesis gravidarum) are normal symptoms and are often found in the first trimester of pregnancy. Almost 50-90% of pregnant women experience nausea and vomiting in the first trimester. One of the pharmacological methods that can be used to treat nausea and vomiting in pregnancy is to consume pyridoxine (vitamin B6) and non-pharmacological among them is to consume Ambon banana (Musa paradisiaca) which contains lots of flavonoids and vitamin B6 which is able to overcome nausea and vomiting in pregnancy.The purpose of this study was to determine the effectiveness of giving Ambon bananas and vitamin B6 in reducing the intensity of nausea and vomiting in first trimester pregnant women at the Lina Hinai Kiri Secanggang Clinic.This research method uses Quasi Experimental research with a cross sectional research design. Data analysis was performed with two independent mean difference test. The research design was used with Two Group Only Post Test Design. The sample technique in this study used a purposive sampling technique and as a sample in this study were pregnant women in the 1st trimester who experienced nausea and vomiting and who came to check their pregnancy at the Lina Hinai Kiri Clinic, Secanggang District as many as 30 people.The results showed that the effectiveness of giving Ambon bananas with Vitamin B6 in reducing the intensity of nausea and vomiting in pregnant women. The table above shows that the frequency of nausea and vomiting in the ambon banana group of all respondents is in the effective category. Likewise, in the group giving vitamin B6, all respondents also included in the effective category, namely with a p-value of 0.001 <=0.05